1998
DOI: 10.1161/01.str.29.12.2600
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Vascular Effects of Cyclooxygenase-2 in Brain

Abstract: Background and Purpose-Cyclooxygenase-2 (COX-2) is an inducible isoform of cyclooxygenase. Several types of brain cells in culture can express COX-2 when treated with lipopolysaccharide (LPS) or some cytokines. LPS produces dilatation of cerebral arterioles in vivo through a mechanism that is partially inhibited by indomethacin. In the present study we examined the hypothesis that LPS causes increased expression of COX-2 in brain as well as COX-2-dependent dilatation of cerebral arterioles. Methods-Cranial win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 49 publications
(42 reference statements)
1
35
0
2
Order By: Relevance
“…However, we found that DEX treatment had no significant effects on COX-1 or -2 protein expression in our samples ( fi g. 4 ). Our data supports the fi ndings of Heinonen et al [9] , Brian et al [28] , and Weidenfeld et al [29] which showed that although DEX decreased vasodilatory prostanoids or arterial diameter in animals exposed to hypercapnia, endotoxin, or lipopolysaccharide treatment, DEX treatment had no effect on baseline levels of COX, vasodilator prostanoids, or lumen size under normocapneic conditions. In addition, studies from Inoue et al [30] showed that glucocorticoid-mediated suppression of COX was dose-and endothelium-dependent , suggesting that DEX at clinically relevant doses applied to endothelium-denuded arteries may not affect COX protein levels.…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that DEX treatment had no significant effects on COX-1 or -2 protein expression in our samples ( fi g. 4 ). Our data supports the fi ndings of Heinonen et al [9] , Brian et al [28] , and Weidenfeld et al [29] which showed that although DEX decreased vasodilatory prostanoids or arterial diameter in animals exposed to hypercapnia, endotoxin, or lipopolysaccharide treatment, DEX treatment had no effect on baseline levels of COX, vasodilator prostanoids, or lumen size under normocapneic conditions. In addition, studies from Inoue et al [30] showed that glucocorticoid-mediated suppression of COX was dose-and endothelium-dependent , suggesting that DEX at clinically relevant doses applied to endothelium-denuded arteries may not affect COX protein levels.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that estrogen reduced IL-1␤-mediated endothelial-dependent cerebral vasodilation; this would perhaps be manifest as diminished hyperemia in the in vivo situation (23). Based on the results of others (3,5,31,36), we suspected that the IL-1␤-mediated decrease in cerebrovascular tone was perhaps governed by COX-2-derived PGE 2 . The endothelial localization of COX-2, the known vasodilatory effects of PGE 2 (14), and the decrease in PGI 2 after IL-1␤ treatment all support this hypothesis.…”
Section: Discussionmentioning
confidence: 59%
“…PGE 2 , PGI 2 , TxA 2 , and PGF 2␣ are known to be vasoactive in the fetal brain (22). In the present study, arterial plasma concentrations of PGE 2 and 6-keto-PGF 1␣ (a stable metabolite of PGI 2 ) were measured as known potent vasodilators (15,30,31). TxB 2 (a stable …”
Section: Discussionmentioning
confidence: 81%